Motivação docente: interfaces, diálogos e possibilidades - Guindani, Marcelo (My University, 2020)
This paper presents the systematization of the study carried out whose research object was the teachers’ motivation and the pedagogical mediation in the elementary school. The investigation here described, inserted in the naturalistic paradigm, qualitative as to the approach, descriptive as to the objectives, made use of the participatory research methodology to seek answers to the problem “Which is the perception of the students regarding the teachers’ motivation and their language, while a stimulating conditionforthe learning in a ninth grade group of the elementary school?”. The data collection for the study proposed occurred from the application of a structured question-naire to 26 ninth grade students. The questionnaires applied were analyzed from the principles of the discursive textual analysis, associated with bibliographic studies, sources which are references in the subject of teacher’s motivation, focusing on the studies of Brophy, Vygotsky, Larrosa, Tardif and Lessard, Freire, Pozo, among others. The discursive textual analysis of the research corpuspro-vided the emergency of the following categories of analysis: The teachers’ knowledge and practic-es: movements that intensify the pedagogical mediation in the classroom;Teachers’ motivation; The communication in the classroom: dialog and learning, and Experiences of the teacher-student rela-tionship. The findings of the research showed that teachers’ motivation is a fundamental element for the pedagogical mediation, which mobilizes meaningful and enduring learning, through the refram-ing of the pedagogical relationship in the classroom. Besides, the investigation allowed verifying that the motivation of a teacher unleashes a series of conditions that provides the learning of the students, through dynamic classes that inspire exchanges of knowledge, making the processes of teaching and learning more dynamic, as well. In addition to that, it was possible to verify that the clear and objective communication and language, allied to the contemporary technologies, enhance the teachers’ performance to awaken the desire for knowledge of the students, besides arousing their curiosity to build up knowledge, qualifying, this way, the pedagogical relationship among the ones involved.
O presente texto apresenta a sistematização do estudo realizado cujo objeto de pesquisa foi a motivação docente e a mediação pedagógica no Ensino Fundamental. A investigação aqui descrita, inserida no paradigma naturalístico, de cunho qualitativo quanto à abordagem, descritiva quanto aos objetivos, lançou mão da metodologia da pesquisa participante para buscar respostas ao problema “Qual a percepção dos estudantes em relação à motivação docente e a sua linguagem, enquanto condição mobilizadora para a aprendizagem em uma turma do nono ano do Ensino Fundamental?”. A coleta de dados para o estudo proposto ocorreu a partir da aplicação de um questionário estruturado a 26 educandos do nono ano. Os questionários aplicados foram analisados a partir dos princípios da análise textual discursiva, aliados a estudos bibliográficos, fontes que são referência no assunto sobre motivação docente, com foco nos estudos de Brophy, Vygotsky, Larrosa, Tardif e Lessard, Freire, Pozo, entre outros. A análise textual discursiva do corpus de investigação propiciou a emergência das seguintes categorias de análise: Os saberes e fazeres docentes: movimentos que intensificam a mediação pedagógica em sala aula; Motivação docente; A comunicação em sala de aula: diálogo e aprendizagem e Vivências da relação professor e aluno. Os achados da pesquisa apontaram para a motivação docente como elemento fundamental para a mediação pedagógica que mobiliza aprendizagens prazerosas e duradouras, através da ressignificação da relação pedagógica em sala de aula. Ainda, a investigação permitiu a constatação de que a motivação de um docente desencadeia uma série de condições que propiciam a aprendizagem dos estudantes, através de aulas dinâmicas que inspiram trocas de saberes, dinamizando os processos de ensino e de aprendizagem. Ainda foi possível constatar que a comunicação e a linguagem clara e objetiva, aliadas às tecnologias contemporâneas, ampliam a performance do docente para despertar a sede do conhecimento por parte dos estudantes, além de aguçar a sua curiosidade para a construção de conhecimentos, qualificando assim a relação pedagógica entre os envolvidos.
Keywords: Professores; Motivação no trabalho; Aprendizagem; Mediação; Teachers; Employee motivation; Learning; Mediation